Retention of doctors in remote, rural and First Nations communities using distributed general practice education: a scalable solution - Giddings, Patrick; O’Sullivan, Belinda; McGrail, Matthew (Frontiers in Medicine, 2025)
The value of distributed training of the medical workforce is well documented. Australia’s Remote Vocational Training Scheme (RVTS) provides a scalable approach to specialist training in general practice that utilizes distance education and remote supervision. RVTS enables trainees to stay in their rural, remote and First Nations communities while working toward specialist certification as a general practitioner. The program, which supports both international and domestically trained graduates through tailored supervision and education, has operated across Australia for 25 years. Trainees are supported both professionally and socially over 4 years. An independent evaluation (2023–24) demonstrated a 78% completion rate among participants who remained in the same rural or remote practice for an average of 5.2 years. Two years after completing the program, 49% were still working in the community where their training commenced, well above documented retention benchmarks for these settings. High levels of participant satisfaction were reported, ranging from 88 to 100% across various indicators. The evaluation found that the program supports retention by eliciting five participant responses: comfort, confidence, competence, belonging, and bonding. Engagement and connection between participants are maintained through accessible technology, real-time support, virtual small-group learning, and twice-yearly in-person workshops. Despite the program’s focus on high-need areas, it is cost-effective compared to similar rural training schemes. The experience of RVTS can inform other countries seeking to enhance rural workforce retention, particularly for underserved populations and migrant healthcare workers. The adaptable structure of the program aligns with the global development goals of the World Health Organization.